The Sumang Tradition among the Gayo Tribe of Central Aceh: An Islamic Education Perspective - Rishna, Musliadi (Didaktika Religia, 2024)
This study examines the educational values inherent to the Sumang tradition of the Gayo people in Central Aceh Regency. Sumang is a tradition replete with knowledge, legal principles and values that inform social interaction, behaviour and character within the Gayo community. A qualitative approach was employed to collect data through observation, in-depth interviews and documentation. The analysis entailed the emergence and reduction of data. The research findings indicate that the educational values embedded in the Sumang tradition encompass respect for customary law, faith, worship and moral principles such as responsibility, modesty, order, loyalty, honesty, self-control, hard work, social concern and peace. Historically, these values were strongly instilled in Gayo families from an early age; however, their practice has declined over time, particularly in urban areas. Nevertheless, in rural communities, the practice of Sumang values remains prevalent, as evidenced by the continued custom of children not sitting knee-to-knee with their parents. This illustrates the continued relevance of the tradition in family life.